Listeriosis Prevention Knowledge Among Pregnant Women in the USA. Issue 1 (2005) - Ogunmodede, Folashade; Jones, Jeffery L.; Scheftel, Joni; Kirkland, Elizabeth; Schulkin, Jay; Lynfield, Ruth
Abstract : Background: Listeriosis is a food-borne disease often associated with ready-to-eat foods. It usually causes mild febrile gastrointestinal illness in immunocompetent persons. In pregnant women, it may cause more severe infection and often crosses the placenta to infect the fetus, resulting in miscarriage, fetal death or neonatal morbidity. Simple precautions during pregnancy can prevent listeriosis. However, many women are unaware of these precautions and listeriosis education is often omitted from prenatal care. Methods: Volunteer pregnant women were recruited to complete a questionnaire to assess their knowledge of listeriosis and its prevention, in two separate studies. One study was a national survey of 403 women from throughout the USA, and the other survey was limited to 286 Minnesota residents. Results: In the multi-state survey, 74 of 403 respondents (18%) had some knowledge of listeriosis, compared with 43 of 286 (15%) respondents to the Minnesota survey. The majority of respondents reported hearing about listeriosis from a medical professional. In the multi-state survey, 33% of respondents knew listeriosis could be prevented by not eating delicatessen meats, compared with 17% in the Minnesota survey ( p = 0.01). Similarly, 31% of respondents to the multi-state survey compared with 19% of Minnesota survey respondents knew listeriosis could be prevented by avoiding unpasteurized dairy products (p = 0.05). As for preventive behaviors, 18% of US and 23% of Minnesota respondents reported avoiding delicatessen meats and ready-to-eat foods during pregnancy, whereas 86% and 88%, respectively, avoided unpasteurized dairy products. Conclusions: Most pregnant women have limited knowledge of listeriosis prevention. Even though most respondents avoided eating unpasteurized dairy products, they were unaware of the risk associated with ready-to-eat foods. Improved education of pregnant women regarding the risk and sources of listeriosis in pregnancy is needed.